Plant Health Characteristics of Creeping Bentgrass Affected by Strobilurin Fungicide Applications and Turfgrass Diseases. Issue 2 (1st March 2016) - Benelli, J.J.; Horvath, B.J.; Brosnan, J.T.; Kopsell, D.A.
Abstract : Previous research has indicated that strobilurin fungicide applications may mitigate the effects of summer heat stress on creeping bentgrass ( Agrostis stolonifera L.). Two multi‐year experiments were conducted in 2011 and 2012 to evaluate plant health characteristics following strobilurin fungicide applications to creeping bentgrass putting greens. In Exp. 1, pyraclostrobin, azoxystrobin, fluoxastrobin, or trifloxystrobin were integrated within a conventional summer fungicide program. In Exp. 2, repeated applications of strobilurin fungicides were evaluated in absence of visible foliar disease. To limit foliar disease, overspray applications of chlorothalonil (2, 4, 5, 6‐tetrachloroisophthalonitrile) and iprodione [3‐(3, 5‐dichlorophenyl)‐N‐isopropyl‐2, 4‐dioxoimidazolidine‐1‐carboxamide] were applied over the experimental units. The plant health characteristics evaluated were visual quality, spectral reflectance, percent green cover, and root morphology. Disease incidence and severity was also quantified visually. In Exp. 1, the nontreated control was similar to strobilurin fungicide programs in all parameters in 2011. In 2012, strobilurin fungicide programs exhibited improved normalized difference vegetation index (NDVI), ratio vegetation index (RVI), turfgrass quality, and percent green cover compared to the nontreated control. Disease severity also increased in 2012 compared to 2011. In Exp. 2, repeated applications of strobilurin fungicides did not affect measured parameters compared to the nontreated control when foliar diseases were managed with fungicides chlorothalonil and iprodione. In these experiments, differences in NDVI, RVI, turfgrass quality, and percent green cover often coincided with differences in disease severity in our evaluations. Under the conditions of these studies, applications of strobilurin fungicides have limited effects on NDVI, RVI, turfgrass quality, and percent green cover in the absence of visible disease.